The effect of digital spillovers and firm characteristics on innovation and productivity in Malaysian manufacturing sector - Liew, Feng Mei (2025)
The productivity of Malaysia's manufacturing sector remains a key government concern, given its role as the backbone of the economy. The emergence of Industry 4.0 has driven the sector to enhance its digital and innovation capabilities to adopt intensive disruptive technologies. Nevertheless, the impact of digitalisation and innovation on Malaysian manufacturing firms remained underexplored. Moreover, limited studies have examined the externalities of digitalisation, potentially leading to an underestimation of the full effect of digitalisation. Thus, this research is motivated to explore the relationships between digital spillovers, innovation and firm productivity in the Malaysian manufacturing sector. The Crepon-Duguet-Mairesse (CDM) model is applied as it allows the analysis of firm-level data. The Heckman selection model, Probit model, and OLS estimator are applied at different stages of the CDM model due to the different nature of the data. The data sample includes a total of 14,723 manufacturing firms, extracted from the Economic Census 2015. These unpublished firm-level data were provided by the Department of Statistics Malaysia upon request in 2020. The estimation results show that the firm characteristics, internal and horizontal digital spillovers are positively related to the innovation activities and firm productivity, as opposed to the forward digital spillover. Meanwhile, the backward digital spillover has a positive impact on the innovation output given the presence of absorptive capacity but exerts a negative effect on the firm productivity. These results reveal that manufacturing firms have lower incentives to conduct innovation when they can receive customers’ feedback quickly via digital platforms. Moreover, manufacturing firms have to readjust and reallocate resources to integrate innovation into production and operations, aligning with supplier requirements and customer demands. These processes might slow down the firm productivity in the short term. Keywords: CDM Model; Digital Spillover; Firm Productivity; Innovation; Malaysia; Manufacturing Firm Subject Area: HD56-57.5 Industrial productivity